A Patient With a Low-grade Mucinous Neoplasm Involving the Ovary and Pseudomyxoma Peritonei Originating in an Isolated Intestinal Duplication. (July 2018) - Simons, Michiel; Ebisch, Inge; de Hullu, Joanne; van Ham, Maaike; Snijders, Marc; de Kievit, Ineke; Bulten, Johan
Abstract : A considerable number of mucinous ovarian tumors are metastatic from other primary tumors, mainly from the gastrointestinal tract, and primary malignant mucinous ovarian tumors are considered rare. Mucinous ovarian tumors occurring within the clinical syndrome of pseudomyxoma peritonei are assumed to almost always originate from the appendix. We describe a patient with a low-grade mucinous tumor involving the ovary in coexistence with pseudomyxoma peritonei, who underwent appendectomy 25 yr earlier. The tumor originated from a rare cystic gastrointestinal duplication found in the mesenteric fat showing adenomatous changes. This illustrates that even in absence of the appendix, mucinous ovarian tumors occurring with pseudomyoma peritonei rarely arise from the ovary.